(untitled) - Singh, Nikky-Guninder Kaur (New York, 2004)
This book, as part of the World Religions Series, discusses the origin of Sikhism, founded 500 years ago in northern India by the mystic Nanak. This book describes the basic tenets of Sikhism and tells the story of its development in India and beyond. The book also examines the recent move toward greater political independence within the Indian nation, the effects of Hindu nationalism on the Sikh community, and issues of cultural adaptation, persecutation, and subsequent education now taking place in the West.
English
Keywords: Sikhism -- Juvenile literature